2015
DOI: 10.1016/j.concog.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Spider stimuli improve response inhibition

Abstract: Anxiety can have positive effects on some aspects of cognition and negative effects on others. The current study investigated whether task-relevant anxiety could improve people's ability to withhold responses in a response inhibition task. Sixty-seven university students completed a modified and an unmodified version of the Sustained Attention to Response Task (SART; Robertson et al., 1997) and provided subjective measures of arousal and thoughts. Anxiety appeared to improve participants' ability to withhold r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
1
13
1
1
Order By: Relevance
“…It was possible that the correlation between commission errors and task-related thoughts was influenced by participants’ response times, as has been noted before (Wilson et al 2015a ). To examine whether this was the case, a partial correlation was conducted.…”
Section: Resultsmentioning
confidence: 77%
“…It was possible that the correlation between commission errors and task-related thoughts was influenced by participants’ response times, as has been noted before (Wilson et al 2015a ). To examine whether this was the case, a partial correlation was conducted.…”
Section: Resultsmentioning
confidence: 77%
“…There was moreover no evidence of an interaction. Although the effect itself was small (ηp 2 = .09), its direction may mean Wilson et al's (2015) alternative explanation that the spider stimuli improved commission errors because spiders are highly salient and detected quickly, not because they were negatively arousing (tension-anxiety inducing), is more plausible. The current findings are consistent with Patton's (2014) finding that stress, in that case through task-relevant shocks, caused firearm operators to make more friendly fire errors (i.e., errors of commission) in a shoot/don't shoot simulation.…”
Section: Discussionmentioning
confidence: 93%
“…Robinson, Krimsky, and Grillon (2013) found that the threat of shock significantly reduces errors of commission on the no-go SART trials relative to the safe condition, suggesting that the negative emotional condition facilitated by threat can actually improve performance, especially when that performance relies on inhibition. This finding was replicated by Wilson, Russell, and Helton (2015), who also suggested that anxiety-provoking stimuli can have positive effects on some aspects of cognition, such us inhibition.…”
mentioning
confidence: 76%
“…Our results suggest negative picture stimuli consume bottom‐up attentional resources to a greater degree causing a larger interference, a finding also reported by other studies (e.g., Ossowski et al ., ). Additionally, the movement of Bias towards the positive spectrum in the negative emotional condition indicates that participants have become more cautious, supporting the conclusion that negative stimuli can increase behaviour that relies on inhibition (Robinson et al ., ; Wilson et al ., ).…”
Section: Discussionmentioning
confidence: 97%